PERANAN GURU MENUMBUHKAN MOTIVASI BELAJAR SISWA DALAM PELAJARAN SEJARAH DI SMA NEGERI 1 SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Sari, Natalia; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the role of teachers to grow students' motivation in learning history in SMAN 1 Sungai Ambawang Kubu Raya.The teacher has an important role in the learning process.The motivation needs to be given by the teacher so that students can be enthusiastic in participating in learning in accordance with the learning objectives to be achieved.The research method used was qualitative with a descriptive form.The data sources in this study were informants from representatives of class X science and social studies students as well as history subject teachers.The data were the results of observations and the results of interviews and documentation.While checking the data was done by triangulation of data that was comparing the results of interviews with observation and documentation.The results showed that the role of the teacher fosters student motivation quite well in the lack of student interest in history subjects in  SMAN 1Sungai Ambawang because the teacher's efforts to foster student learning motivation include explaining learning goals, giving praise, making gifts, giving penalties, using method, and give enthusiasm.As well as the inhibiting factors faced in increasing student learning motivation, namely lack of time allocation, lack of student learning motivation, different abilities, learning media that are not optimal, and family environment. Keywords:  Motivation, SMAN 1 Sungai Ambawang, Students,Teachers